Using the World-Wide Web to obtain large-scale word norms: 190,212 ratings on a set of 2,654 German nouns - Lahl, Olaf; Göritz, Anja S.; Pietrowsky, Reinhard; Rosenberg, Jessica (Behavior research methods, 2009)
This article presents a new database of 2,654 German nouns rated by a sample of 3,907 subjects on three psycholinguistic attributes: concreteness, valence, and arousal. As a new means of data collection in the field of psycholinguistic research, all ratings were obtained via the Internet, using a tailored Web application. Analysis of the obtained word norms showed good agreement with two existing norm sets. A cluster analysis revealed a plausible set of four classes of nouns: abstract concepts, aversive events, pleasant activities, and physical objects. In an additional application example, we demonstrate the usefulness of the database for creating parallel word lists whose elements match as closely as possible. The complete database is available for free from ftp://ftp.uni-duesseldorf.de/pub/psycho/lahl/WWN . Moreover, the Web application used for data collection is inherently capable of collecting word norms in any language and is going to be released for public use as well.